Two voices that look to be one: Political ideologies and ethnic identities in the Memories of Juan Bautista Tupac Amaru - Grillo, María Teresa (2014)
The Memorias of Juan Bautista Tupac Amaru (1825) is a unique and autobiographical text, written by the brother of José Gabriel Condorcanqui, Túpac Amaru II, who was taken prisoner after the defeat of the Andean leader and released decades later, in times of the Latin American emancipation. It brings together the memories of the Andean uprising and the ideals of Spanish American independence led by Creoles. Thisarticle suggests that the Memories constitute a “collaborative autobiography” (Lejeune1989) whose textual markers let us identify an Andean voice and another Creole. The duality of the narrative voice reveals the importance of the moment of enunciation in the textualization of Juan Bautista’s memories, particularly in the textual constructions referred to the Enlightenment ideas and concepts about race. Through fissures caused by the double enunciation, it is possible to make an approach of the prevailing political ideas in the text, as well as the perceptions of ethnic identities expressed by the subjects of enunciation.